INFLUENCE OF PHYSICOCHEMICALS AND TEXTURES IN HEAVY METALS ACCUMULATION IN LAKE NOKOUE (BENIN) - KAKI, CHRISTOPHE; KELOME, Nelly Carine; GUEDENON, Patient; EDORH, A. Patrick (My University, 2014)
Toxic metals (cadmium, lead, copper and arsenic) assessment was carried out in water and sediments samples of Lake Nokoué. Except for water, a group of sediment samples was mineralized before the analysis with atomic absorption spectrophotometer. The second group of sediment samples was processed for texture analysis. The results revealed that for the physico-chemical characteristics, the pH ranged from 6.5 to 8.5 while identified textures were mud, sand, sandy mud and muddy sand. On the average, heavy metals concentration in water increased from 0.01 to 10.1 mg/L, while lead increases from 5.84 to 8.47 for arsenic. In water, copper showed low concentrations at all sites while cadmium was below the detectable limits. The mean sediments concentration ranges were Cd (0.56 to 22.07 mg/L), Pb (3.2 to 13.94mg/L), Cu (11.51 to 54.39 mg/L) and As (ND to 436.81 mg/L). Besides, the pattern of trace elements accumulation in the textures revealed that sandy mud and sand sediments recorded high concentrations of arsenic with mud having high cadmium concentrations while sandy mud and muddy sand surfaces had high concentrations of copper. The result also shows no correlation between heavy metal and pH except for arsenic in Lake Nokoué (BENIN).
Keywords: Nokoue Lake; Pollution; Heavy Metal; Texture; Physicochemical Parameters